Biochar Valorization from Oregano and Citronella Residues: Impacts on Radish Growth and Methyl Orange Dye Removal - Marwa Rammal; Chaden Haidar; Ghenwa Kataya; Akram Hijazi; Lara Yazbek; Khodor Haidar; Mohammad H. El-Dakdouki (Proceedings)
In recent years, the rapidly growing essential oil industry has generated residues that, if improperly managed, can harm ecosystems by contaminating soil and water [...]